Editorial: Islam in Asia and Europe (Al-Jamiah: Journal of Islamic Studies, 2013)
The subjects of discussion in this edition of Al-JÄmiâah are mostly modern Indonesia with the exception of Al Makinâs paper on early Islam and Miftahurrohim N. Sarkun on classical Islamic jurisprudence. To begin with, Nina Nurmila overviews the extent to which modern Indonesian Quranic and tradition exegetes gives new meaning to the basic sacred text of Islam. Indeed Nurmila finds that the issues of gender have attracted the attention of Indonesian intellectuals, who argue for gender equality and menâs and womenâs equal role both at home and work. In fact, many Indonesian exegetes reject the inferiority of women at home with regard to conventional understanding that men are seen superior in domestic leadership. Pribadi, on the other hand, highlights the identity of Madurese in relation to the way in which santri culture always revives in this island. According to Pribadi, the main components in the Madurese culture and politics are kiai or ulama (religious leader), pesantren (traditional Islamic boarding school), and NU (Nahdlatul Ulama, the biggest Islamic organization in Indonesia). These factors always played critical role from the Dutch colonial time down to the reform period. At the same time, the Madurese never lose their traditional ethnic values and traditions.